Combined medical therapy in the treatment of allergic rhinitis: Systematic review and meta-analyses - Chitsuthipakorn W. (2023)
Background: Antihistamines (ATH) and intranasal corticosteroids (INCS) are primary treatments for patients with allergic rhinitis (AR). When monotherapy of either primary treatment fails to control symptoms, combined medical therapy is an option. In this meta-analysis we assessed the additional effects of different medical combinations compared with primary treatments. Methods: Systematic searches on PubMed and EMBASE were updated on November 4, 2021. Randomized, controlled trials comparing the effects of combinations with monotherapy were included. There were 7 comparisons: (1) ATH-decongestant vs ATH; (2) ATH-leukotriene receptor antagonist (LTRA) vs ATH; (3) INCS-ATH vs INCS; (4) INCS-LTRA vs INCS; (5) INCS-decongestion vs INCS; (6) INCS-saline irrigation vs INCS; and (7) ATH-saline irrigation vs ATH. Data were pooled for meta-analysis. Outcomes were composite nasal symptom score, composite ocular symptom score, quality of life (QoL), and adverse events. Results: Fifty-three studies were included. Compared with ATH alone, the ATH-decongestant combination improved composite nasal symptoms; ATH-LTRA improved nasal symptoms in patients with perennial AR; and ATH-nasal saline improved both symptoms and QoL. Compared with INCS alone, the INCS-intranasal ATH combination improved nasal symptoms, ocular symptoms, and QoL; INCS-LTRA improved ocular symptoms but not nasal symptoms; and INCS-nasal saline improved QoL but not symptoms. There were no additional effects observed from adding oral ATH or topical decongestant to INCS. Conclusion: After ATH monotherapy fails to control symptoms, addition of decongestant, saline, or LTRA can improve the outcomes. When INCS monotherapy is ineffective, addition of intranasal ATH can improve nasal symptoms; LTRA can improve ocular symptoms, and saline irrigation can improve QoL.